The Value of Fecal Microbiota Transplantation in the Treatment of Ulcerative Colitis Patients: A Systematic Review and Meta-Analysis - Yantian Cao (Gastroenterology Research and Practice, 2018)
Background and Aims. Fecal microbiota transplantation (FMT) has challenged the traditional management of ulcerative colitis (UC) in recent years, while it remained controversial. We aimed to provide a systematic protocol of FMT treatment on UC. Methods. Studies reporting on FMT treatment in UC patients were performed. A fixed-effect model was used to assess the efficacy of FMT. Results. Eighteen studies were enrolled (n=446). A pooled proportion of patients who received FMT had a significant efficacy compared to the placebo group (odds ratio (OR): 2.73, P=0.002) with a low risk of heterogeneity (P=0.59, I2=0%). The Mayo score decreased to 5 points in a state of mild–moderate activity after FMT treatment, and the optimal range of the Mayo score baseline was 6–9 for FMT administration. Then, the baseline of the Shannon diversity index (SDI) had a negative correlation with the clinical response rate (R=−0.992, P=0.08) or remission rate (R=−0.998, P=0.036), and the optimal diversity of bacteria was at 7 days to one month. Moreover, the colonoscopy delivery and unrelated fecal donor had slight superiorities of FMT treatment. Conclusion. FMT treatment had a higher efficacy and shorter time-point of early assessment of effectiveness on UC patients compared to traditional therapies. And the optimal FMT delivery and donor were colonoscopy delivery and unrelated donor in clinical practice.